2022
DOI: 10.1155/2022/2876474
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Correlation Analysis between Emotion Control and Professional Self‐Efficacy of Singing Artists Based on Multidimensional Environment

Abstract: The tertiary industry occupies a large area in China’s economic system, and it plays an important function in the growth of China’s economic development. It is of positive significance to study the relationship between emotional labor and occupational self-efficacy of singing artists in the tertiary industry. This paper mainly studies the correlation between the emotional labor of singing artists and their professional self-efficacy and analyzes the strength of the correlation. This paper selects 150 singing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…For example, emotional labor was shown to negatively correlate with artists’ PSE. 20 Cultural context, suboptimal supervision, as well as aversive working experiences, all exhibited a certain degree of association with clinical trainees’ PSE. 40 Importantly, PSE, as an important predictor of performance among healthcare professionals, 41 can be modifiable through participation in discipline-specific courses or sessions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, emotional labor was shown to negatively correlate with artists’ PSE. 20 Cultural context, suboptimal supervision, as well as aversive working experiences, all exhibited a certain degree of association with clinical trainees’ PSE. 40 Importantly, PSE, as an important predictor of performance among healthcare professionals, 41 can be modifiable through participation in discipline-specific courses or sessions.…”
Section: Discussionmentioning
confidence: 99%
“… 17 Learning SE can be instrumental in enhancing the professional performance of undergraduate medical students. 18 Moreover, previous studies in nursing science, 19 singing artists, 20 and mental health therapists 17 all showed that professional SE was a valid surrogate of discipline-specific clinical performance. However, the existing literature rarely addresses how to assess learning SE from a multidimensional perspective among postgraduate learners, especially in nephrology.…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%